2014
DOI: 10.1007/s10508-014-0279-1
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Sexual Dysfunction Among HIV-Positive and HIV-Negative Men Who Have Sex With Men: Mediation by Use of Antidepressants and Recreational Stimulants

Abstract: Erectile dysfunction (ED) and other forms of sexual dysfunction are highly prevalent among HIV+ men who have sex with men (MSM). Research has not previously identified the mechanisms by which depression may be associated with sexual dysfunction among HIV-positive and HIV-seronegative (HIV-negative) MSM. The present study examined the role of antidepressant use, stimulant use, and smoking as mediators of the relation between depression and sexual dysfunction among HIV-positive and HIV-negative MSM. Participants… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 60 publications
1
28
0
2
Order By: Relevance
“…Cigarette smoking is associated with ED in the general population ( Kovac, Labbate, Ramasamy, Tang, & Lipshultz, 2015 ) and prevalence of smoking continues to be very high among HIV-infected people ( Parks, Hernandez-Ramirez, Silverberg, Crothers, & Dubrow, 2016 ). Nevertheless, in a previous study smoking duration was related to ED only in HIV-negative men ( Hart et al, 2015 ). More studies should be developed to evaluate better this variable in men with HIV infection.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Cigarette smoking is associated with ED in the general population ( Kovac, Labbate, Ramasamy, Tang, & Lipshultz, 2015 ) and prevalence of smoking continues to be very high among HIV-infected people ( Parks, Hernandez-Ramirez, Silverberg, Crothers, & Dubrow, 2016 ). Nevertheless, in a previous study smoking duration was related to ED only in HIV-negative men ( Hart et al, 2015 ). More studies should be developed to evaluate better this variable in men with HIV infection.…”
Section: Discussionmentioning
confidence: 75%
“…However, this relationship remained controversial, since other researchers reported contradictory data ( Ende et al, 2006 ; Lallemand et al, 2002 ; Wang et al, 2013 ). Additional factors frequently mentioned include older age ( Asboe et al, 2007 ; Guaraldi et al, 2007 ; Moreno-Pérez et al, 2010 ; Pérez, Moreno, Navarro, Santos, & Palacios, 2013 ), duration of exposure to ART ( Asboe et al, 2007 ; Moreno-Pérez et al, 2010 ), and emotional disturbances and medications to treat them ( Asboe et al, 2007 ; Guaraldi et al, 2007 ; Hart et al, 2012 ; Hart et al, 2015 ; Pérez et al, 2013 ). The objectives of this study were to evaluate erectile dysfunction (ED) in a wide sample of men and to explore sociodemographic, clinical, and emotional contributing factors.…”
mentioning
confidence: 99%
“…Reported rates of erectile dysfunction in the MSM population range from 33-74%, compared to 0-18% in the general population, and may be increased by antidepressant use. 66 Monitoring for antidepressant adherence and side effects, including sexual dysfunction, is highly advised. Antidepressants such as vilazodone or bupropion, which are associated with significantly less sexual dysfunction, may be recommended.…”
Section: Compounding Adverse Effectsmentioning
confidence: 99%
“…16,17 Poor mental health can in turn negatively affect sexual functioning. [18][19][20] A small number of studies among adult MSM have identified associations between various minority stressors and sexual difficulties/ dysfunction/dissatisfaction. Internalized homonegativity, or negative feelings one has towards one's self as a sexual minority, and other forms of self-stigma (e.g., conflict about one's sexual identity, difficulty being intimate with someone of the same gender) are more consistently related to both difficulties/dysfunction and dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%